Brill's companion to Alexander the Great - Roisman, Joseph, 1946- (Brill's Companions to Classical Studies., 2003)
Many important issues surrounding Alexander the Great's conquest have captured the interest of scholars and general readers since antiquity. This book acquaints us with these issues and their current interpretations, and opens up new directions of investigation as it confronts them. It covers a broad range of topics: the ancients' representations of the king in literature and art; Alexander's relations with Greeks, Macedonians, and the peoples of Asia; the military, political, sociological, and cultural aspects of his campaigns; the exploitation of his story by ancient philosophers to argue a moral point and by modern communities to affirm or contest ethnic and national identities. This volume will be of interest to scholars and nonspecialists alike and serve as a standard reference work for years to come.